Test Voltage Optimization and Safety Margin of Insulation Tools for Live Working of UHV AC Transmission Lines - Kai ZHU; Yuqun FANG; Guangkai YU (Zhongguo dianli)
In view of the problem that the test voltage of live working insulation tools for 1 000 kV UHV AC transmission lines is too high, causing abnormal damage to the work tools, we made an in-depth analysis of the power frequency and operating overvoltage level for the live working condition of 1 000 kV AC transmission lines. And at the same time, a research was carried out on the voltage selection and safety margin for the 1 000 kV UHV live working insulation tool test. After comprehensive analysis, the reasonable test voltage and safety margin range are put forward, and the proposed revision values are verified by a number of tests including power frequency withstand voltage test, insulation material electrical performance test and live working safety test, which have fully proved the rationality of the proposed revision values.